Analysis of Halal Awareness Among Students in the Faculty of General Sciences and the Faculty of Religious Sciences (Case Study: Halal Food Court at UIN Sunan Kalijaga) - mansyur; Setyaningsih, Ira; Kurniawati, Dwi Agustina (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2025)
This study investigates the overall level of halal awareness among students at the State Islamic University (UIN) Sunan Kalijaga Yogyakarta, compares the level of awareness between students from religious studies faculties and general studies faculties, and identifies the most dominant dimension—knowledge, attitude, or behavior—in each group. Employing a quantitative approach with a comparative design, the research collects data through a closed-ended questionnaire based on a 5-point Likert scale, complemented by documentation studies. Data analysis involves validity and reliability testing, descriptive statistical analysis, normality and homogeneity tests, and an Independent Sample t-Test. The results reveal high halal awareness across both groups, with a t-value of -0.721 and a significance level of p = 0.472 (p > 0.05), indicating no statistically significant difference between faculties. Dimension-based analysis shows that attitude is the most dominant aspect, reflecting strong positive perceptions and beliefs about the importance of halal products, while the behavior dimension records comparatively lower scores, indicating an intention–behavior gap. These findings suggest that the university’s Islamic environment fosters a shared awareness of halal principles among students, regardless of academic discipline, and highlight the need for practical interventions to strengthen the consistent application of halal practices in daily life.